Actinomycetoma by Actinomadura madurae: Clinical characteristics and treatment of 47 cases - Alexandro Bonifaz; Andrés Tirado-Sánchez; Denisse Vazquez-Gonzalez; Javier Araiza; Rigoberto Hernández-Castro (Wolters Kluwer Medknow Publications, 2021)
Context: Mycetoma is a chronic, granulomatous disease caused by fungi (eumycetoma) or aerobic filamentous actinomycetes (actinomycetoma). Actinomadura madurae is one of the most frequent actinomycetes. Aim: The study aims to provide an update on clinical, diagnostic, therapeutic, and outcome data for patients with actinomycetoma in a single center in Mexico. Settings and Design: This was a retrospective study of 47 cases diagnosed with actinomycetoma. Subjects and Methods: The cases were selected from a total of 536 mycetoma obtained during 35 years (from 1985 to 2019). Clinical data were retrieved from the clinical records of our department. Microbiological data were obtained from our Mycology laboratory. Statistical Analysis: Frequencies and percentages were used for categorical variables. Normality was determined with the Kolmogorov-Smirnov test. We used means and medians to describe the variables. Results: Forty-seven patients with actinomycetoma were included; female:male ratio 1.9:1; median age 38 years. The foot was the most affected region in 76.5% of cases. The bone invasion was observed in 89%. The time between symptoms onset and diagnosis was 5.5 years. Grain detection by direct examination was positive in 95% of cases. The most commonly used, as well as the most effective treatment scheme was streptomycin + sulfamethoxazole-trimethoprim with dapsone. Sixty-three percent (30 patients) achieved clinical and mycological cure, and 10.6% (5 patients) had treatment failure. Conclusions: We highlight the importance of designing therapeutic strategies to standardize treatments and gain more experience to improve the care of these patients.